Factors Affecting Student Academic Performance : A Systematic Review - Long, Wang; Chen, Chwen Jen (The International Journal on Studies in Education (IJonSE), 2025)
This systematic review synthesizes evidence on factors affecting Student Academic Performance (SAP), focusing on individual, family, school, and social dimensions. A comprehensive search using Google Scholar covered studies from 2000 to July 2024. Thematic synthesis revealed that individual factors such as age, gender, motivation, self-efficacy, and test anxiety significantly impact SAP. Family influences, including parents’ education, income, and involvement, were also crucial. School-related factors like teachers’ qualifications, self-efficacy, and teaching methods emerged as important, while social factors such as peer relationships, social support, private tutoring, and socioeconomic status also played key roles. However, inconsistencies were found in the magnitude and direction of some effects, indicating the need for further exploration of these influences. The educational relevance and implications of this research are significant, as it highlights a comprehensive understanding of the factors influencing SAP across multiple dimensions—individual, family, school, and social. Practically, this research provides crucial insights for educators, policymakers, and stakeholders to implement targeted interventions that foster supportive learning environments, ultimately enhancing student outcomes.